Prevalence of Polypharmacy and Inappropriate Medication in Adults With Intellectual Disabilities in a Hospital Setting in Switzerland - Lonchampt, Sophie; Gerber, Fabienne; Aubry, Jean-Michel; Desmeules, Jules; Kosel, Markus; Besson, Marie (Frontiers in Psychiatry, 2021)
Background: Polypharmacy and inappropriate prescription are frequent in vulnerable and multi-morbid populations. Adults with intellectual disability (ID) are at risk of being polymedicated because they often present with multiple comorbidities and challenging behaviours. Aim: The objective of this study was thus to evaluate the prevalence of potentially inappropriate medications (PIM) and polypharmacy in a hospital unit dedicated to adults with ID. Methods: A 10-month prospective observational study took place at a hospital unit specializing in the care of adults with ID in Geneva, Switzerland. Once a week, health and prescription data were collected and screened for PIM according to preset definitions. Results: Fourteen patients consented to participate, leading to twenty hospitalization events assessed during the study. Hospitalizations lasted 12.8 weeks on average. ID severities ranged from mild to profound, all degrees of severity being equally represented. One hundred percent of the patients were polymedicated (defined as 5 drugs or more prescribed simultaneously). A mean number of 9.4 drugs were prescribed per week, including 5.3 psychotropic drugs. The number of prescribed drugs remained stable throughout the hospitalizations. Antipsychotics were the most prescribed drug class (19% of all prescribed drugs), followed by benzodiazepines (13%) and laxatives (12%). A total of 114 PIM were recorded with an average of 5.7 PIM per hospitalization. Conclusions: This study showed that polypharmacy and inappropriate prescription are very common in adults with ID, even though the literature and expert positions advocate for deprescription in these patients. Specific prescribing and deprescribing guidelines are needed for that specific population.